Pengaruh Penerapan Peer Tutoring Terhadap Hasil Belajar Kognitif Biologi Siswa SMA Negeri 5 Bone - Karisma, Afianty; Mustami, Khalifah; Ngitung, Rosdiana (Biology Teaching and Learning, 2020)
Abstract. This research applied Quasy Experiment which aimed to explain the influence of Peer Tutoring Model toward students’ Biology Cognitive learning outcome at SMAN 5 Bone. The population of this research was the second semester of the XI IPA students at SMAN 5 Bone. The samples of this research were the XI IPA1 and XI IPA2 students with the total number of 45 students. The samples were selected by purposive sampling technique. The data were obtained through learning outcome test. The result of the research showed that (1) students’ learning outcome in the control class were getting enhancement at the average of 40,32 and were at the level of the highest category, high category, and moderate category and was at moderate category (2) students’ learning outcome in the experimental class were improved at average 49,85 and were at the level of the highest category, high category, and moderate category and was at high category (5) application of Peer Tutoring model significantly influenced the student’s learning outcomes of Biology.Keywords: peer tutoring model, cognitive learning outcome